2017
DOI: 10.1515/amm-2017-0357
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution During Laser Surface Alloying of Ductile Cast Iron with Titanium

Abstract: Diode laser surface alloying process was used to the in-situ synthesis of TiC-reinforced composite surface layers on the ductile cast iron substrate. The obtained composite surface layers were investigated using optical and scanning electron microscopy, and XRD diffraction.It was found that the morphology and fraction of TiC phase is directly dependent upon both the concentration of titanium in the molten pool and also the solidification rate. With increasing titanium content, the fraction of TiC increases, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…During all trials, the laser spot was located on the top surface of SM, and the fast-axis of the laser beam was set parallel to the scanning direction. Based on previous work [ 23 , 24 , 25 ], the laser power and traverse speed were held constant at 1500 W and 1.25 mm/s, respectively. The powder feed rates depended on the type of the alloying material and are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During all trials, the laser spot was located on the top surface of SM, and the fast-axis of the laser beam was set parallel to the scanning direction. Based on previous work [ 23 , 24 , 25 ], the laser power and traverse speed were held constant at 1500 W and 1.25 mm/s, respectively. The powder feed rates depended on the type of the alloying material and are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…High C contents in cast iron substrates provide excellent conditions for the in situ formation of MMC surface layers via LA, with elements that tend to form carbides. Several studies on the LA of cast iron substrates have focused on the in situ synthesis of TiC-reinforced layers (TRLs) by introducing Ti into the molten pool [ 16 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. From the point of view of the wear properties, the microstructure of the synthesized TRLs should contain a martensitic matrix with homogeneously-dispersed TiC precipitates [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Among them, TiC has the following advantage for cast iron: it can be readily synthesized in a laser melt pool; thus, it significantly reduces the carbon content in the matrix. [13][14][15] Janicki et al 14 found that the morphology and fraction of the TiC phase directly depends on the concentration of titanium in the melt pool and on the solidification rate. With an increased titanium content, the fraction of TiC increases, whereas the fraction of cementite decreases.…”
Section: Introductionmentioning
confidence: 99%